ANALISIS STRATEGI PENINGKATAN DAYA SAING KOMODITAS KENTANG (Solanum tuberosum) DI DESA SEMBALUN KABUPATEN LOMBOK TIMUR NUSA TENGGARA BARAT - Dwi Marianti 1); Arifuddin Sahidu 2); I Wayan Suadnya 2) (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2017)
ABSTRACT Potato is one of the commodities of superior commodity which is very commercial. In order to maintain it, it is demand to increase the competitiveness of potato commodity. The purpose of this research is to formulate and determine the right strategy to increase the competitiveness of potatos commodities (Atlantic variety and Granola varietiy) through AHP. This research uses descriptive method and the data collection techniques used are survey and interview. The analysis of data used are: descriptive analysis, SWOT analysis, and analytical hierarchy process (AHP). The results shows that there are five structural potato supply chains, internal factors and external factors have each eight criteria as alternative strategies and AHP shows that the strategies of internal factors that improve infrastructure to potato production, increase the availability of seed potatoes, expand information market, optimize the use of cultivation Sembalun potential area, enhance and utilize the experience cultivation of potato farmers, improve the quality of the potatoes, take advantage of the availability of labor in potatoes post-harvest processing, and reduce over-production and strategies of external factors employing the skills of potato farmers, follow the level competition, increase production opportunities in the dry season, reduce the level of extreme climate, take advantage of the government policy, increase production to meet consumer demand, reduce pests and diseases and reduce and minimize the occurrence of fluctuations in the potatoes price level. ABSTRAK Kentang merupakan salah satu komoditas pangan unggulan yang sangat komersial.untuk mempertahankannya maka dituntut adanya upaya peningkatan daya saing terhadap komoditi kentang. Penelitian ini menggunakan metode deskriptif dan teknik pengumpulan data adalah survei dan wawancara. Analisis data yang digunakan adalah: analisis deskriptif, SWOT, dan analisis hierarki proses (AHP). Hasil penelitian menunjukkan bahwa terdapat lima struktur rantai pasok komoditas kentang, faktor internal dan faktor eksternal memiliki masing-masing delapan kriteria sebagai alternatif strategi dan AHP menunjukkan bahwa strategi dari faktor internal yaitu meningkatkan sarana dan prasarana produksi kentang, meningkatkan ketersediaan bibit kentang, memperluas informasi pasar, mengoptimalkan penggunaan areal budidaya Sembalun yang potensial, meningkatkan dan memanfaatkan pengalaman budidaya petani kentang, meningkatkan kualitas kentang, memanfaatkan ketersediaan tenaga kerja dalam proses pasca panen kentang, dan mengurangi over produksi serta strategi dari faktor eksternal yaitu memanfaatkan ketrampilan petani kentang, mengikuti tingkat persaingan, meningkatkan peluang produksi pada musim kemarau, mengurangi tingkat iklim ektrim, memanfaatkan adanya kebijakan dari pemerintah, meningkatkan produksi untuk memenuhi permintaan konsumen, mengurangi hama dan penyakit serta mengurangi dan meminimalisir terjadinya tingkat fluktuasi harga kentang.